Evaluation Of The Activity Of Aqueous And Alcoholic Extract And Essential Oil Of Eucalyptus incrassata Toward Some Biological Characteristics Of The Water Mold Saprolegnia ferax - Ali, B. Z.; Mahde, T. S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The study was conducted to evaluate the antifungal activity of the aqueous and alcoholic extract and the essential oil of E. incrassata leaves toward some biological characteristics of the water mold S. ferax. Chemical analysis of the plant leaves using HPLC showed the content of several active compounds included 1,8-Cineole, Terpineal, Citronellal, Phellendrene and Citiric acid. Treatment of the fungus growing on solid media containing different concentrations of the extracts showed significant gradual decrease in radial growth with the increasing concentration, and the effect varied with the different extracts. Treatment of the fungus grown in distilled water on sesame seeds with different concentration of both extracts and the essential oil caused significant delay in production of zoosporangia and oogonia with the increasing concentration, which showed effect on asexual and sexual reproduction. Results of treating encysted zoospores with different concentrations of both extracts and essential oil showed significant gradual reduction in percentage zoospore germination with the increase of concentration. Generally, the essential oil showed higher activity at the lower concentration followed by the alcoholic extract then the aqueous.